Diversity and phylogenetic analysis of Chaetomium fungus from southeastern Tibet - YUE Haimei; ZHUANG Hua; PAN Zhaohui; GONG Wenfeng (浙江大学学报. 农业与生命科学版, 2017)
Chaetomium Kunze is mainly distributed in cellulose-containing substrates in the nature, including soil, plant residue, excrement of birds, omnivorous animals and rodents. Persistent organic compounds can be degraded by cellulase produced by Chaetomium Kunze, which also has antagonistic effects on certain microorganisms in the soil. However, little has been known about Chaetomium in Tibet. Therefore, a systematic research on resource distribution of Chaetomium in Tibet is necessary and urgent.In this study, 355 samples of soil, plant residue and animal manure were collected from five regions of southeastern Tibet, in which plant residue and animal manure were separated by tissue separation, and soil samples were separated by dilution separation method. SPSS 13.5 software was used to analyze the diversity index of Chaetomium spp. from different regions, and 36 strains were preliminarily classified according to Arx system. The nucleotide sequence polymorphisms of rDNA-ITS and β-tubulin gene were analyzed by DnaSP version 5.0. The rDNA-ITS and β-tubulin gene sequences were used to analyze the diversity of Chaetomium species in southeastern Tibet.The results showed that a total of 36 strains were successfully isolated from the 355 samples, and the average isolation rate was 10.14%. The diversity index data indicated that both the diversity index and species evenness index of Chaetomium spp. in Nyingchi was the highest, with the value of 1.178 5 and 0.605 6 respectively. But the richness index of Chaetomium was the highest in Chamdo, with the value of 0.861 4. Differences of dominant populations of Chaetomium were observed among the five regions: the dominant population in Gongbogyamda County, Medog County and Chamdo City, Zayü County, and Nyingchi County was C. globosum, C. funicola, C. bostrychodes, and C. convolutum, respectively. According to the morphological characteristics, the 36 strains were assigned to eight species. Moreover, rDNA-ITS sequences and β-tubulin gene were applied to conduct the diversity analysis, and the result showed that the variation sites, haplotype numbers, haplotype diversity, nucleotide diversity index and nucleotide difference of β-tubulin gene were significantly different from rDNA-ITS sequences, while β-tubulin gene showed greater base variability. The phylogenetic tree of rDNA-ITS and β-tubulin genes indicated that the 36 isolates were divided into seven groups. The two gene fragments can not only distinguish the species of Chaetomium with different morphologies (such as C. indicum, C. megalocarpum, C. globosum and C. funicola), but also those with very similar morphological characteristics (such as C. indicum and C. erectum) and some species hard to distinguish. However, several species such as C. convolutum, C. bostrychodes and C. nigricolor can’t be distinguished by rDNA-ITS and β-tubulin genes, which still need combining more gene fragments to differentiate.In conclusion, the results confirm the rich resources of Chaetomium fungus in southeastern region of Tibet, providing data for abundant resources of Chaetomium in Tibet, and laying a foundation for the exploitation of the metabolites of Chaetomium.